Chronic stress in adolescence differentially affects cocaine vulnerability in adulthood in a selectively bred rat model of individual differences: role of accumbal dopamine signaling. (4th May 2021) - Aydin, Cigdem; Frohmader, Karla; Emery, Michael; Blandino Jr, Peter; Akil, Huda
Abstract: Stress during adolescence has profound effects on the onset and severity of substance use later in life. However, not everyone with adverse experiences during this period will go on to develop a substance use disorder in adulthood, and the factors that alter susceptibility to substance use remain unknown. Here, we investigated individual differences in response to stress and drugs of abuse using our selectively bred high-responder (bHR) and low-responder (bLR) rats. These animals model extremes of temperamental tendencies and differ dramatically in both stress responsiveness and addiction-related traits. The present study investigated how environmental interventions in the form of a chronic variable stress (CVS) regimen in early adolescence interact with the bHR/bLR phenotype to alter behavioral sensitization to cocaine in adulthood. We also determined whether accumbal dopamine signaling is involved in the interaction of stress history and cocaine by assessing the mRNA levels of dopamine D1 (D1R) and D2 (D2R) receptors. Our results showed that CVS history alone had enduring and phenotype-specific effects on accumbal dopamine signaling. Importantly, adolescent stress had opposing effects in the two lines- decreasing the locomotor response to cocaine challenge in bHRs but increasing this measure in bLRs. Moreover, these opposing effects on cocaine sensitivity following adolescent CVS were accompanied by parallel effects in the accumbal dopamine system, with prior stress and cocaine exposure interacting to decrease D2R mRNA in bHRs but increase it in bLRs. Overall, these findings indicate that environmental challenges encountered in adolescence interact with genetic background to alter vulnerability to cocaine later in life. Lay Summary: Stress experienced during adolescence affects the onset and severity of drug dependence later in life. However, not everyone with adverse experiences during this period will go on to develop SUD in adulthood. Using a rat model of innate differences in emotional reactivity, this study shows that the interplay between individual temperament and previous experience of adolescent stress/trauma determines whether an individual will be vulnerable or resilient to develop SUDs later in life. In addition, the present study shows that the dopamine D2 receptor in the brain's reward center, nucleus accumbens, may be implicated in this interplay.